Revisão da seção setacea do gênero Batrachospermum (Rhodophyta, Batrachospermales) - Rossignolo, Natalia Leocadio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Section Setacea of the genus Batrachospermum was recognized as a monophyletic group in a recent revision of the order Batrachospermales. However, its taxonomic status was not clearly determined because it was positioned within a group named Australasica composed by taxa from Australia and New Zealand. Previous studies combining molecular and morphological data focused only on the phylogenetic relationships among the major groups (genera or sections), whereas approches aiming to evaluate the number of species were initiated just recently and are still scarce and poorly sampled. Based on this background, the following hypotheses were tested in this study: 1) the section Setacea represents a monophyletic group within the order Batrachospermales; the recognition of the group associated to the fact that the genus Batrachospermum is paraphyletic could result in the raising of the section to a higher taxonomic level (possibly genus); 2) the species presently recognized in the section based on morphological characters will be confirmed by molecular evidence; in addition, other species (particularly cryptic species) are expected to be found and recognized within the section.This study aimed to: 1) infer the phylogenetic relationships of section Setacea with other groups (genera and sections) of the Batrachospermales, as well as the inter and intra-specific limits of variation for the species within the section based on sequence analysis for the rbcL and cox1 barcode region: 2) elaborate a revisionary study by reevaluating the diagnostic taxonomic characters for the species of the sectionin the light of the new molecular data. Fifteen samples were analyzed, thirteen from southern and southeastern Brazil and two from other continents (Asia - Japan; Europe - Spain). The specimens were collected in waters with low to moderate temperatures, slightly acidic, turbulent and mean to moderate oxygen concentrations (oligotrophic and oligosaprobic...

A seção Setacea foi reconhecida como grupo monofilético na revisão recente da ordem Batrachospermales. Porém, seu status taxonômico não pode ser determinado, porque posicionou-se dentro do grupo denominado Australasica, composto por táxons da Austrália e Nova Zelândia. Estudos anteriores combinando dados moleculares e morfológicos enfocaram apenas as relações filogenéticas entre os grupos maiores (gêneros ou seções) e abordagens visando avaliar o número de espécies só foram iniciadas muito recentemente e são ainda escassas e baseadas em poucas amostras. Dessa maneira, as seguintes hipóteses foram testadas neste estudo: 1) a seção Setacea do gênero Batrachospermum constitui grupo monofilético dentro da ordem Batrachospermales; o reconhecimento desse grupo associado ao fato de Batrachospermum ser parafilético poderá resultar na elevação desta seção para um nível superior (possivelmente um gênero); 2) as espécies atualmente reconhecidas na seção com base em caracteres morfológicos serão confirmadas pelos dados moleculares; além dessas espécies, outras (particularmente espécies crípticas) deverão ser encontradas e reconhecidas dentro da seção. Este estudo teve como objetivos: 1) inferir as relações filogenéticas da seção Setacea com os outros grupos (gêneros e seções) da ordem Batrachospermales, bem como os limites de variação inter e intra-específica das espécies dentro da seção, com base na análise das sequências do gene rbcL e da região de barcode do gene cox1; 2) elaborar estudo de revisão para a seção Setacea por meio da reavaliação dos caracteres taxonômicos diagnósticos para espécies deste grupo, à luz dos novos dados moleculares. Foram analisadas 15 amostras, sendo 13 provenientes das regiões sul e sudeste do Brasil, uma do Japão e outra da Espanha. Os espécimes foram coletados em águas com temperaturas baixas a moderadas, ligeiramente ácidas a neutras, agitadas..
Keywords: Botânica; Filogenia; Alga vermelha - Classificação; Código de barras de DNA taxonômico; Batrachospermales; Batrachospermum